2014
DOI: 10.1590/1413-81232014193.19052013
|View full text |Cite
|
Sign up to set email alerts
|

Namoro na adolescência no Brasil: circularidade da violência psicológica nos diferentes contextos relacionais

Abstract: Namoro na adolescência no Brasil: circularidade da violência psicológica nos diferentes contextos relacionais

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
2
33

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 45 publications
1
21
2
33
Order By: Relevance
“…In contrast to studies on dating aggression among the general youth population (Arriaga & Foshee, 2004;Oliveira et al, 2014), and to a study on aggression among street youth (Baron et al, 2007), an increased number of peers who abuse dating partners did not predict a greater frequency of IPV in a study of Brazilian street youth. The study cites the influence of broader aggressive norms in the group, such as using violence to resolve conflicts (Antonio et al, 2012).…”
Section: Friends/peerscontrasting
confidence: 68%
See 3 more Smart Citations
“…In contrast to studies on dating aggression among the general youth population (Arriaga & Foshee, 2004;Oliveira et al, 2014), and to a study on aggression among street youth (Baron et al, 2007), an increased number of peers who abuse dating partners did not predict a greater frequency of IPV in a study of Brazilian street youth. The study cites the influence of broader aggressive norms in the group, such as using violence to resolve conflicts (Antonio et al, 2012).…”
Section: Friends/peerscontrasting
confidence: 68%
“…Witnessing inter-parental violence (Vaz, 2012); Verbal aggression from the mother and father; and psychological violence among parents, siblings, circularity of violence (Oliveira et al, 2014) Models of relationships from families of origin in which aggression is seen as inherent to relationships (Aldrighi, 2004) Family-related factors: Family attitudes and behaviors that are unequal and/or justify violence (i.e., authoritarianism, patriarchy, punishment, unidirectional respect and others in which masculine ideals and values are valued over feminine ones) (Rivera Sierra, 2012); inter-family (ENDESA, 2013) Low tendency to seek help (Soares et al, 2013;Minayo et al, 2011) Low help-seeking proclivities: only 5% of girls aged 15-19 reported IPV to the police or an authority (compared to 30% of women aged 45-49 -no data reported on boys/men and helpseeking) (ENDESA, 2013) For victimization of women: young age, low socioeconomic status (Lundgren and Amin, 2015); older age and having children (Instituto Nacional de la Juventud, 2013); Being a race other than white (Foshee et al, 2001) Risk factors according to a study on sexual coercion: Female sex (girls are also more likely to experience a first experience of sexual coercion or abuse at a younger age compared to boys, and by older men); being a race other than white (Moraes et al, 2006) Age: girls aged 15-19 years more likely to have suffered physical and psychological violence within the past 12 months (cumulatively, older women were more likely to have ever experienced violence since age 15) (ENDESA, 2013) Risky sexual practices (Lundgren and Amin, 2015); among adolescent girls -sexual risk behaviors (e.g., first intercourse before age 15 years, pregnancy Dating violence was directly associated with risky sexual behaviors among sexually experienced adolescent girls, particularly non-white girls, in a US study …”
Section: Family-related Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the interest in this subject may be attributed to two significant factors: (1) the high prevalence rates of dating violence in several countries (Straus, 2004;Dorotéia, 2013;Haynie et al, 2013;Oliveira, Assis, Njaine, & Pires, 2014) and (2) the psychosocial impact of dating violence on the victims, which is considered a public health concern (Haynie et al, 2013).…”
Section: Introductionmentioning
confidence: 99%